2016
DOI: 10.1007/s10531-016-1081-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultural monuments and nature conservation: a review of the role of kurgans in the conservation and restoration of steppe vegetation

Abstract: Steppe is among the most endangered biomes of the world, especially in Eastern Europe, where more than 90 % of original steppes have been destroyed due to conversion into croplands, afforestation and other human activities. Currently, steppe vegetation is often restricted to places unsuitable for ploughing, such as ancient burial mounds called kurgans. The aim of our study was to collect and synthesise existing knowledge on kurgans by a review of research papers and grey literature. The proportion of kurgans c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(162 citation statements)
references
References 40 publications
1
123
0
22
Order By: Relevance
“…This could be primarily due to livestock change and the impact from feeding, trampling, etc., which reduces the surface area for photosynthesis and changes the vegetation structure, thus affecting plant community characteristics [15,16]. Previous studies have shown that vegetation within forbidden grazing regions, which are not impacted by feeding and trampling, grow rampantly; hence, the average height, total aboveground biomass and species richness are significantly greater than in the grazing region [17,18]. However, some studies have also pointed out that the dominant species in the forbidden grazing region will directly or indirectly control the vitality of other species.…”
Section: Effects Of Different Grazing Systems On Plant Community Charmentioning
confidence: 99%
“…This could be primarily due to livestock change and the impact from feeding, trampling, etc., which reduces the surface area for photosynthesis and changes the vegetation structure, thus affecting plant community characteristics [15,16]. Previous studies have shown that vegetation within forbidden grazing regions, which are not impacted by feeding and trampling, grow rampantly; hence, the average height, total aboveground biomass and species richness are significantly greater than in the grazing region [17,18]. However, some studies have also pointed out that the dominant species in the forbidden grazing region will directly or indirectly control the vitality of other species.…”
Section: Effects Of Different Grazing Systems On Plant Community Charmentioning
confidence: 99%
“…The identified threats to steppes have not affected the whole biome evenly; priorities in steppe conservation and restoration are therefore likely to vary regionally . Deák et al (2016) and Dembicz et al (2016) show that in the European part of the steppe and forest steppe zone, only small, fragmented patches of steppe remained. They identified a need for the restoration of steppe habitat to increase landscape-scale connectivity.…”
Section: Conservation Status Threats and Restorationmentioning
confidence: 99%
“…They identified a need for the restoration of steppe habitat to increase landscape-scale connectivity. Deák et al (2016) suggest that steppe vegetation can persist even in heavily degraded landscapes at certain structures, such as kurgans, road verges, and field margins, which can act as sources of species (i.e. donor sites for restoration).…”
Section: Conservation Status Threats and Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of grassland ecosystems into croplands, afforestation, urbanization, and other detrimental human activities is a global problem [10]. Increasing human population has led to increased need for food production and this has resulted in expansion of croplands; close to 20% of savanna grasslands in Africa has been converted to cropland and urban areas [9].…”
Section: Introductionmentioning
confidence: 99%